Systematic approach to paired ceramic coatings deposited by oxygen fuel and metal in a tribological application - K.A. Habib; D.L. Cano; Emilo Rayón; J. Serrano-Mira; José V. Abellán-Nebot; I. Cervera (Journal of Materials Research and Technology)
This study investigated nanostructured Al2O3 and Al2O3–TiO2 composite coatings (e.g., 3, 13 and 40% TiO2, mass fraction) deposited by the oxygen fuel (OF) spraying technique. The coatings exhibited varying hardness values, ranging from 705 HV0.2 for Al2O3-40%T to 1317.9 HV0.2 for Al2O3. To compare the behaviours of the coated specimens, the mechanical properties and effects of hardness ratio on the lubrication regimes were studied using the Stribeck curve. The higher TiO2 content contained in the Al2O3–TiO2 coating system yielded relatively inferior mechanical properties but lower porosity (ranged between from 18.3% A to 0%T to 1.64% A-40%T) and initial and final hardness ratio (16.2% Al2O3 to 9.2% Al2O3–40%TiO2). Microstructural and phase analyses showed that this finding can be attributed to the special phase, Al2TiO5, and to the pre-existing microcracks in the coating. Thus, Al2O3–13%TiO2 exhibited better characteristics for mechanical applications and oil film stability as compared with pure Al2O3 and 3% and 40% TiO2 coatings. This study provides a reference for the design of Al2O3–TiO2 ceramics with good wear resistance and a minimal friction coefficient under lubrication conditions. The strain hardening produced on the surfaces of the worn discs and the hardness ratio determined the tribological properties of the friction pairs. In summary, this work analysed the friction and wear properties of four ceramic coatings and their counterpart metallic discs under lubrication conditions using Stribeck curve, to provide an experimental basis for screening optimal materials for the key friction and wear pairs of industrial design and applications. The proposed methodology may assist in predicting variations in lubrication regime parameters (Stribeck curve) by controlling the hardness ratio.